“A ‘Bon François’ Desirous of the Glory of the King”: Intra-Catholic Anti-Jesuitism and the Collapse of the Port Royal Mission, 1610-1613 - Wachtel, Joseph R. (Acadiensis, 2020)
This article examines the collapse of the Jesuit mission to Port Royal, Acadia, in 1613 through the lens of anti-Jesuit pamphleteering popular in France. After the colony’s collapse, its proprietor, Jean de Poutrincourt, wrote an anonymous Factum explaining in detail how two Jesuit missionaries, Pierre Biard and Enemond Massé, conspired against France to bring down the settlement. Although the Factum is not factually accurate, in the context of French Catholic politics in the aftermath of the Wars of Religion the dispute demonstrates the transfer of European debates over Catholicism and the Reformation across the Atlantic in New France’s earliest years.